Factors Associated with Knowledge of Congenital Anomalies Among Pregnant Women in Nepal - Shrestha, Rina; Shrestha, Nistha; Paudel, Smriti (NPRC Journal of Multidisciplinary Research, 2025)
Background: Congenital anomalies, also known as birth defects, refer to structural or functional abnormalities present at birth. These conditions include anatomical deformities, metabolic disorders, and physiological defects that can lead to life-threatening complications, long-term disabilities, and significant physical, social, and cognitive challenges (WHO, 2024). Birth defects are a leading cause of neonatal mortality and stillbirths globally, with a higher burden in low- and middle-income countries, including Nepal. Despite their severe consequences, many pregnant women lack adequate knowledge about congenital anomalies, their risk factors, and preventive measures. Methods: A cross-sectional descriptive study was conducted to assess the knowledge level regarding congenital anomalies and associated factors among pregnant women attending the Antenatal Outpatient Department of Paropakar Maternity & Women’s Hospital, Thapathali, Kathmandu. Using a non-probability purposive sampling technique, 167 pregnant women were enrolled. Data was collected through a semi-structured questionnaire developed based on research objectives, literature review, and expert consultation. Results: The study revealed significant gaps in knowledge among pregnant women. Only 11% had good knowledge about congenital anomalies, while 49% demonstrated poor understanding. The remaining 40% had moderate knowledge. A chi-square test was performed, yielding a p-value of 0.15, indicating no significant statistical association between variables. Conclusion: The findings highlight that most pregnant women in the study had poor knowledge about congenital anomalies. To address this gap, targeted health education programs during antenatal visits and awareness campaigns through mass media are essential. Improving maternal knowledge can contribute to early prevention, better pregnancy outcomes, and a reduction in the prevalence and incidence of congenital anomalies in Nepal.